Dynamic supply response of farm households in Ethiopia - Bachewe, Fantu Nisrane; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2015)
We study the dynamics of the supply response of smallholder grain producers to changes in crop prices and costs of production in Ethiopia. We develop an intertemporal acreage demand allocation model of a representative household under a rational expectations hypothesis. An estimable acreage demand equation is derived and estimated for teff, an important staple grain in Ethiopia. We apply systems and linear dynamic panel data models to a data set covering a time period marked with remarkable agricultural and macroeconomic growth and smallholder-focused economic policies. The results indicate that teff acreage demand increases faster than permanent increases in real teff prices, and it rises by a third of temporary price increases. Moreover, teff acreage demand declines with increases in the opportunity cost of producing teff.